The Use of Jigsaw to Improve the Student's Vocabulary for The Eight Year Students of MTs Miftahul Ulum - Khoirul Umam Muzayyanah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
Abstract Vocabulary is an essential means in conducting communication. Developing students’ vocabulary is one of the important tasks for English teachers. The researcher as a teacher used jigsaw as a technique in teaching vocabulary. Mastering English vocabularies is the first key to master English well. Jigsaw strategy is an efficient way to learn the course material in a cooperative learning style. The purpose of this research is to improve the students’ vocabulary using jigsaw. This is a classroom action research. The result shows that after implementing the jigsaw, the students’ vocabulary had a strong improvement. The students’ improvement can be seen from the students’ participation during the lesson and their score. The use of jigsaw had given a positive effect to the students’ vocabulary ability. The effect was not only for their vocabulary but also for their motivation and their interest to English.